Pengawasan Pemeliharaan Jalan Kabupaten oleh Bidang Bina Marga Dinas Pekerjaan Umum Kabupaten Tabanan Studi Kasus Kecamatan Selemadeg Barat - Mantik, Ki Juang; Yasintha, Putu Nomy; Winaya, I Ketut (CITIZEN CHARTER, 2019)
ABSTRACT In the Regulation of the Minister of Public Works No.13/PRT/M/2011. The Tabanan Regency Government through the Highways Sector Office of Public Works is obliged to carry out monitoring and reporting activities on the implementation of road maintenance aimed at maintaining road conditions and improving the quality of roads in Tabanan Regency, especially Selemadeg Barat.The unit of analysis of this research is monitoring,namely the Highways Sector Tabanan Regency. In this study, it had been described the surveillance criteria proposed by Siagian in Silalahi, namely process, implementation, organi ation and plan. The Informants in this study were determined by using purposive sampling. The results of this study indicate that in the implementation of monitoring of road maintenance carried out by the Highways Sector Office of Public Works Office of Tabanan Regency has not proceeded properly. Keywords: Monitoring, road Maintenance